Platelet‐rich plasma versus corticosteroid injections in the management of patients with rotator cuff disease: A systematic review and meta‐analysis. Issue 1 (31st October 2022) - Adra, Maamoun; El Ghazal, Nour; Nakanishi, Hayato; Smayra, Karen; Hong, Sam S.; Miangul, Shahid; Matar, Reem H.; Than, Christian A.; Tennent, Duncan
Abstract: Platelet‐rich plasma (PRP) is an alternative to corticosteroid (CS) injections in managing rotator cuff disease. This meta‐analysis investigated differences between PRP and CS for function and pain scores in significance and minimal clinical important difference (MCID). A literature search of Ovid Cochrane Library, Medline, Embase, Epub, and Scopus was conducted from inception to October 28, 2021. Eligible studies reported patients older than 18 years with a diagnosis of rotator cuff disease. This review was registered in PROSPERO (ID: CRD42021278740). Twelve studies met eligibility criteria ( n = 639) of patients receiving either PRP or CS. At short‐term follow‐up, a difference favored CS compared to PRP in baseline change for disability of arm, shoulder, and hand (DASH) score (MD = −5.08, 95% CI: −8.00, −2.15; p = 0.0007; I 2 = 0%) and simple shoulder test (SST) (MD = 1.25, 95% CI: 0.33, 2.18; p = 0.008; I 2 = 0%). At intermediate follow‐up, a difference favored PRP to CS baseline change of the DASH score (MD = 3.41, 95% CI: 0.67, 6.15; p = 0.01; I 2 = 0%). At medium‐term, a difference favored PRP to CS baseline change of the American Shoulder and Elbow Surgeons Shoulder (ASES) score (MD = −4.42, 95% CI: −8.16, −0.67; p = 0.02; I 2 = 0%). Both treatments achieved individual MCID for each score. Despite favoring CS at short‐term follow‐up and PRP at intermediate‐ and medium‐term follow‐up, functional and pain scores did not demonstrate any clinical difference between the two treatment modalities in management of rotator cuff disease at all follow‐up periods.